Added value of narrow band imaging and confocal laser endomicroscopy in detecting Barrett’s esophagus neoplasia - Jayasekera, C.; Taylor, A. C. F.; Desmond, P. V.; Macrae, F.; Williams, R. (Endoscopy, 2012)
Background and study aims: Advances in endoscopic imaging techniques have enabled more accurate identification of subtle mucosal abnormalities. The aim of the study was to assess the accuracy of predicting high grade dysplasia (HGD) and intramucosal cancer (IMC) in mucosa predicted as being nondysplastic vs. dysplastic by high definition white light endoscopy (HD-WLE), narrow band imaging (NBI), and confocal laser endomicroscopy (CLE).Patients and methods: A cross-sectional study was performed in a tertiary referral setting between February 2010 and September 2011. A total of 50 consecutive patients who were referred to St Vincent’s Hospital for management of dysplastic Barrett’s esophagus were included. A prediction of likely histology was made for each mucosal point (four-quadrant every 1 cm and any visible mucosal abnormality), first with HD-WLE, followed by NBI, and finally CLE. Biopsies were taken at all of these points.Results: A total of 1190 individual biopsy points were assessed. At histology, 39 biopsy points were found to harbor HGD and 52 biopsy points harbored IMC. For the detection of HGD/IMC the sensitivity, specificity, and accuracy were: HD – WLE, 79.1 %, 83.1 %, and 82.8 %; NBI, 89.0 %, 80.1 %, and 81.4 %; and CLE, 75.7 %, 80.0 %, and 79.9 %, respectively. All mucosal points with IMC and all patients with HGD were detected by targeted biopsies guided by HD-WLE and NBI without the need for random Seattle protocol biopsies.Conclusions: HD-WLE in combination with NBI is highly accurate in the detection of HGD/IMC. Performing targeted biopsies in the surveillance of Barrett’s esophagus is possible in expert centers.